Elementary science teacher educators learning together: catalyzing change with educative curriculum materials and vignette writing - Asim, S; Davis, J; Kinskey, M; Lavender, H; Murrary, J; Obery, A; Sherwood, C.-A.; Voss, S (Innovations in Science Teacher Education, 2023)
Keywords: dept.cur; peer-reviewed; ⛔ No DOI found

Extending Student (R)esponse to (E)ngagement in a Bilingual Classroom: An Analysis of Identity-Infused Classroom Discourse - Ferraro, Marisa (Empowering Students Through Multilingual and Content Discourse, 2023)
The growing diversity of students in schools has raised important questions regarding how students learning English and discipline-content simultaneously succeed academically. This challenge has been exacerbated by disparities in resources among multilingual communities throughout the COVID-19 pande...
Keywords: dept.cur